Illuminating al-Gharb: LA-ICP-MS characterization of 10th- to 13th-century CE glass from Silves Castle, Portugal - Ana Cadena-Irizar; Rosa Varela Gomes; Marcia Vilarigues; Nadine Schibille (Boletín de la Sociedad Española de Cerámica y Vidrio)
Little is known about consumption patterns of glass and the development of regional glass production during the Islamic period in present-day Portugal (Gharb al-Andalus). This work considers the glass finds from Silves Castle (Portugal), dated to the 10th to mid-13th century CE. The chemical composition of the glass assemblage was determined by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), and lead isotopic analysis was performed on selected high lead samples. The results were compared to legacy data to identify possible cross-links and trade networks with other contemporary Islamic sites in the Iberian Peninsula and the Eastern Mediterranean. The glass assemblage from Silves proved to be rather heterogeneous, with two major compositional groups and three so-called soda-rich Iberian lead glass samples. Group 1 shows characteristics of glass of Iberian origin but with distinct recycling markers, while Group 2 resembles glass from 10th-century Córdoba with little recycling. Judging from these similarities, the main supply seems to have been largely covered by Iberian glass. The predominance of Iberian compositions illustrates the decline in trade relations between the city and the Eastern Mediterranean regarding glass products that affected even an elite context such as the Castle of Silves. Resumen: Poco se sabe sobre las dinámicas de consumo de vidrio y el desarrollo de la producción vidriera regional durante el periodo islámico del actual territorio portugués (Gharb al-Andalus). En este trabajo analizamos los materiales vítreos recuperados en el castillo de Silves (Portugal), datados entre el siglo X y mediados del siglo XIII de nuestra era. La composición química del material se determinó mediante espectrometría de masas con fuente de plasma de acoplamiento inductivo (LA-ICP-MS), y fue complementada con análisis isotópicos en determinadas muestras. Los resultados se compararon con bases de datos existentes de otros yacimientos islámicos contemporáneos de la Península Ibérica y del Este del Mediterráneo para identificar posibles vínculos y redes comerciales. El conjunto vítreo de Silves resultó ser bastante heterogéneo, con dos grupos composicionales distintos y tres muestras identificadas como vidrio de plomo con alto contenido de sodio, también presente en otros sitios ibéricos. El Grupo 1 presenta rasgos propios de los vidrios producidos en el ámbito islámico peninsular, pero con evidencias claras de procesos de reciclado. Por su parte, el Grupo 2 guarda similitudes con los vidrios de Córdoba del siglo X, y en su mayoría, con escasos indicios de reciclaje. A juzgar por estas afinidades composicionales, el abastecimiento principal parece haber dependido en gran medida del vidrio ibérico, lo que ilustra el declive de las relaciones comerciales con el Este del Mediterráneo en lo que a productos de vidrio se refiere.